1969
DOI: 10.3109/00365526909180620
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Arteriosclerosis in Elderly People

Abstract: Gastric Arteriosclerosis in Elderly People. Scatzd. f. Gastroenf. 4 , 387-389. A series of 103 autopsied patients over thc age of 60 were examined for arteriosclerosis in gastric and various extragastric vessels. Nine of them had significant arteriosclerosis in the gastric vessels, against 89 patients with such changes in the coronary arteries. It is concluded that gastric arteriosclerosis is rare even in patients over 60 with a high rate of arteriosclerosis in extragastric vessels. The importance of gastric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It should be noted here that to achieve a satisfactory patency and avoid competition of flow, the stenosis in the target vessel for GEA grafting needs to be at least 80%. Other advantages of the GEA are its very low susceptibility to arteriosclerosis, 26 its ability to improve flow in response to augmented myocardium demand, 27 and its length being long enough to reach any coronary artery. 28 Potential disadvantages of the use of the GEA are the increased risk of postoperative ileus and the risk of jeopardizing the graft in case a laparotomy is needed with time.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted here that to achieve a satisfactory patency and avoid competition of flow, the stenosis in the target vessel for GEA grafting needs to be at least 80%. Other advantages of the GEA are its very low susceptibility to arteriosclerosis, 26 its ability to improve flow in response to augmented myocardium demand, 27 and its length being long enough to reach any coronary artery. 28 Potential disadvantages of the use of the GEA are the increased risk of postoperative ileus and the risk of jeopardizing the graft in case a laparotomy is needed with time.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, even in the different vessel layers some changes were more severe in some regions than in others. In this study, we used an arteriosclerotic classification described by Larsen et al The authors reported that the gastroduodenal artery apparently has less arteriosclerosis than the coronary artery. In addition, they graded arteriosclerotic changes in four degrees as we did, in grades I–IV (from normal to severely diseased) .…”
Section: Discussionmentioning
confidence: 99%
“…The intimal changes and the degree of arteriosclerosis were classified based on the previously established classification by Larsen et al and were organized into four categories: 0, normal; I, intimal thickening of the thickest part occupying less than 25% of the luminal diameter (mild); II, intimal thickening occupying between 25 and 50% of the luminal diameter (moderate); III; intimal thickening occupying more than 50% of the luminal diameter (severe); and IV, total occlusion, atherosclerotic change with ulceration or calcification (very severe).…”
Section: Methodsmentioning
confidence: 99%
“…Arteriosclerosis of the GEA was found to be less frequent than in the coronary artery [ 12 ]. In our previous study, the GEA and ITA used in CABG were examined pathologically and moderate to severe arteriosclerosis was noted in 8% of GEA grafts and 1% of ITA grafts [ 13 ].…”
Section: Anatomy Histology and Physiologymentioning
confidence: 99%